EFEKTIVITAS BADAN PENGAWAS PEMILIHAN UMUM DALAM PENANGANAN PELANGGARAN PADA PEMILIHAN UMUM TAHUN 2019 - M. Arafat Hermana; Dwi Putra Jaya (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2021)
Abstract: There are still many violations in every general election such as administrative, criminal and ethical code violations in Bengkulu City. There are two problems examined in this thesis reviewing the Effectiveness of the General Election Supervisory Agency in handling violations in the general election and sanctions given by the Election Supervisory Agency in settlement of handling violations that occur in the general election. This research used the normative-empirical legal research method, namely legal research on the enforcement or implementation of normative legal provisions in action on any particular legal event that occurs in the community. Normative research is a legal research that examines written law from aspects of theory, history, philosophy, comparison, structure and composition, scope and material, general explanation of article by article, formality and the strength of binding a law but does not bind the applied aspects or its implementation whereas the Empirical research is an unwritten positive legal research concerning the behavior of community members in community relations. The resolution in handling of violations in the general election is still less effective because there are still many violations that still occur at the time the general election takes place and the sanctions given have no clear firmness and have not caused a deterrent effect for who committed violations. Keywords: Effectiveness, Supervision, Violations